Empowering Home-Based Bakery Industry in Probolinggo through Production Capacity Enhancement and Digital Marketing Training (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Micro, small, and medium enterprises (MSMEs) in the bakery sector often face production and marketing limitations that reduce competitiveness. Wijaya Bakery, a home-based bakery in Probolinggo, experienced inefficiency in production and reliance on traditional promotion. This program introduces an empowerment model integrating production technology enhancement, business management training, and digital marketing activation. The approach addresses immediate operational issues while supporting long-term sustainability. Using a user-centered design approach, the program followed four stages: identifying target users, analyzing needs, designing solutions, and evaluation. Interventions included the provision of equipment (oven, mixer, proofer, trolley), training in production and business management, digital marketing workshops, and continuous mentoring. Evaluation relied on production records, social media monitoring, and customer satisfaction surveys. The program increased production capacity by 88.6%, from 700 to 1,320 breads per day, and reduced production time for small breads (2.8 to 1 day) and large breads (5 to 3 days). Training improved partner competence in hygiene, quality control, financial recording, and medium-term planning. Digital marketing activation on Instagram, WhatsApp, and YouTube Shorts raised customer engagement by 20% in two months. A customer satisfaction survey indicated high ratings (>85%) with 100% willingness to recommend products. The integration of production technology, management training, and digital marketing effectively empowered Wijaya Bakery and strengthened its competitiveness. This model offers a replicable approach for similar MSMEs to improve resilience and market reach.